Trauma, Poetry, Fuck The Jante Law - Creativity as a Means of Survival - Anna Iachino 1961- (2022)
Over the last sixty years, I have discovered many different aspects of my creativity. My two-year studies, Master’s in Music in the NAIP program, at Iceland University of the Arts have led me on a path of self-discovery and self-knowledge from a turbulent past to this present reflective time. Through an autoethnographic recollection, I will share and explore my creative research, writing poetry to songwriting to poetry with electronics. In this self-analysis, I will dive into my research question: How might creative expression in writing and music become a means of survival? STUDNI-Student Grant Fund SU